The psychological impact of river water quality on communities: An analysis of lead (Pb), BOD, and COD levels - Tumiwa, Vebriola; Sondakh, Ricky C; Umboh, Jootje (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: River water quality is influenced by various pollutants, particularly organic and chemical contaminants resulting from anthropogenic activities. In rural and peri-urban areas, domestic waste is a major contributor to the decline in water quality, which may pose risks to environmental and public health. Purpose: To analyze river water quality based on lead (Pb), Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD) parameters, and to identify the psychological impacts on communities living along the river. Method: A quantitative descriptive study with an observational approach was conducted using the grab sampling method. Water samples were collected from three points representing upstream, midstream, and downstream sections. Laboratory analyses were performed, and the results were compared with the water quality standards established by Government Regulation of the Republic of Indonesia No. 22 of 2021. The study was carried out from November to December 2025. Results: BOD values at all sampling points (7 mg/L upstream, 12 mg/L midstream, and 6 mg/L downstream) exceeded the permissible limits, indicating non-compliance with water quality standards. In contrast, COD values ranged from 7 to 8 mg/L across all points and remained within acceptable limits. Pb concentrations ranged from 0.001 to 0.006 mg/L, which were also below the regulatory threshold. Conclusion: The findings indicate that the deterioration of water quality in the Sawangan River is primarily driven by organic pollution rather than chemical or heavy metal contamination. These results highlight the need for improved domestic waste management and continuous monitoring to maintain river water quality. Keywords: Biochemical Oxygen Demand (BOD); Chemical Oxygen Demand (COD); Lead (Pb); Organic Pollution; River Water Quality.